Respon Dosis Pupuk Terhadap Pertumbuhan dan Hasil Kacang Tanah (Arachis hypogaea L.) Varietas Domba: Response of Fertilizer Doses on Growth and Yield of Peanuts (Arachis hypogeae L.) Domba Varieties - Ahmad Sarjana; Lina Budiari; Zainal Mutaqin; Joko Restuono (Politeknik Negeri Lampung, 2023)
This study aims to determine the dose of fertilizer on the growth and yield of peanut plants and to get the best dose of phonska and urea fertilizers to increase the production of peanut plants. The usefulness of this research is as information material for readers to develop and increase the yield of peanut plants through the use of fertilizers. As well as being able to add scientific references about various doses of fertilizer in the cultivation of peanut plants. The research design used a group randomized block design (RBD) consisting of 4 levels of treatment and 3 replicates, namely: P1 (phonska 300 kg/ha and urea 150 kg/ha); P2 (phonska 225 kg/ha and urea 112.5 kg/ha); P3 (phonska 150 kg/ha and urea 75 kg/ha); and P4 (phonska 75 kg/ha and urea 37.5 kg/ha). There were significant differences in the observation variables of the number of filled pods, wet pod weight, and dry pod weight between treatment 1 (P1), which is a combination of phonska fertilizer dosage of 300 kg/ha and urea fertilizer 150 kg/ha, and treatment 4 (P4), which is a combination of phonska fertilizer 75 kg/ha and urea fertilizer 37.5 kg/ha.